Spiritual Intelligence From The Shariah Perspective And Its Importance In The Military Profession In Malaysia - Raja Raziff Raja Shaharuddin; Daud Mohamed Salleh; Muhammad Syukri Haji Zahari; Elmi Baharudin; Zahimi Zainol Abidin (Global Academic Excellence (M) Sdn Bhd, 2026)
Indexed by MYCITE